Functional Interpretation of Alright? as a Lecture Question: a Multimodal Analysis - Hakobyan, Nare (Armenian Folia Anglistika, 2018)
The article is devoted to the revelation of how crucial the multimodal analysis is in the functional interpretation of Alright? as a lecture question, because it is only thanks to the multimodal analysis that the functional interpretation of the question becomes complete and comprehensive. Moreover, we will attempt to answer the question whether Alright? is a true question or not.